Seasonal Variation in Soil and Herbage CO2 Efflux for a Sheep-Grazed Alpine Meadow on the North-East Qinghai-Tibetan Plateau and Estimated Net Annual CO2 Exchange - Yuan, Hang; Matthew, Cory; He, Xiong Zhao; Sun, Yi; Liu, Yang; Zhang, Tao; Gao, Xiaoye; Yan, Caiyu; Chang, Shenghua; Hou, Fujiang (Frontiers in Plant Science, 2022)
The Qinghai-Tibetan Plateau is a vast geographic area currently subject to climate warming. Improved knowledge of the CO2 respiration dynamics of the Plateau alpine meadows and of the impact of grazing on CO2 fluxes is highly desirable. Such information will assist land use planning. We measured soil and vegetation CO2 efflux of alpine meadows using a closed chamber technique over diurnal cycles in winter, spring and summer. The annual, combined soil and plant respiration on ungrazed plots was 28.0 t CO2 ha–1 a–1, of which 3.7 t ha−1 a−1 occurred in winter, when plant respiration was undetectable. This suggests winter respiration was driven mainly by microbial oxidation of soil organic matter. The winter respiration observed in this study was sufficient to offset the growing season CO2 sink reported for similar alpine meadows in other studies. Grazing increased herbage respiration in summer, presumably through stimulation of gross photosynthesis. From limited herbage production data, we estimate the sustainable yield of these meadows for grazing purposes to be about 500 kg herbage dry matter ha−1 a−1. Addition of photosynthesis data and understanding of factors affecting soil carbon sequestration to more precisely determine the CO2 balance of these grasslands is recommended.